We Need to Talk About Fancy Dress: Connections (and Complications) Between the Catwalk and Fancy Dress Costume. (2nd January 2022) - Wild, Benjamin Linley
Abstract: Many fashion designers repudiate the influence of fancy dress within their work. This marginalization likely reflects a socialized attitude that fancy dress is a short-lived, skill-less and superficial spectacle that lacks credibility. Many scholars and fashion commentators concur. They argue that this sartorial form and the circumstances in which it is worn are not affective, that it does not influence how wearers perceive themselves and others, and thereby lacks a fundamental characteristic of most clothing. Arguing that fancy dress is affective, this article reappraises the connections between dressing up and fashion design. It summarizes, first, the long-standing interplay between fancy dress and contemporary vogues. Second, the article considers the presence of non-normative fashions on the modern catwalk. Two suggestions are made to further academic discussion. First, recent discussions about 'critical' and 'experimental' fashions can become more globally and culturally relevant if they are expanded to include fancy dress costume. Second, fancy dress costume can be more usefully understood, and readily incorporated within academic studies, if it is acknowledged that this term is not unidimensional and encompasses a variety of garments, reflecting the diverse motivations of people who choose to dress up. The article uses recent clothing collections as case studies.